Survivability of the thermographic phosphors YAG:Pr and SMP:Sn in a premixed flame. (30th April 2021) - Kopf, A; Bardi, M; Kohler, E; Endres, T; Bruneaux, G; Schulz, C
Abstract: The survivability of two thermographic phosphors, YAG:Pr 3+ and SMP:Sn 2+ ((Sr, Mg)3 (PO4 )2 :Sn 2+ ), in a combustion environment is studied in the post-flame regime of a premixed propane/air flame. While the laser-induced luminescence of YAG:Pr 3+ can be exploited for in situ temperature measurements in the exhaust gas above the flame, there is no in situ detectable luminescence for SMP:Sn 2+ for any reaction conditions within the stability limits of the flame. The phosphor particles are recaptured above the flame and ex situ analyzed for chemical or structural changes using microscopic analysis (SEM/EDX) and x-ray diffraction. The microscopic analysis of post-flame YAG:Pr 3+ does not show any alteration, whereas morphology and chemical composition of SMP:Sn 2+ have been modified upon passing through the reaction zone, which is responsible for the loss of its luminescence properties.